Improvement of Simple Test Cell Design for Cathode Microstructure Study in Tubular-Type Sodium–Metal Chloride Batteries - Byeong-Min Ahn; Cheol-Woo Ahn; Byung-Dong Hahn; Jong-Jin Choi; Yang-Do Kim; Sung-Ki Lim; Joon-Hwan Choi (Batteries, 2022)
Sodium–metal chloride batteries are suitable alternatives in battery energy storage systems (BESSs), since they are widely known as a type of high-safety battery. To accurately analyze the cathode microstructure of sodium–metal chloride batteries, in this study, we demonstrate the improved tubular-type simple test cell. This improved tubular-type simple test cell was supplemented from the setbacks of our previous test cell, such as a leak, Ni current collector wavering, and sodium wicking. Through testing of the improved test cells, we focus on cathode microstructure analysis, owing to the elimination of the external failure factors mentioned above. The group of improved test cells have a lower capacity gap of 9.5% in the 1st cycle than the capacity gap of previous test cells (37.2%). This result indicates the advancement of reproducibility. Moreover, the improved test cell has a long life of approximately 7200 h by changing the previous test cell structure. In particular, it is expected that this improved tubular simple test cell can advance the research of tubular-type sodium–metal chloride batteries in a small and academic laboratory.